Manajemen strategi dalam konteks bisnis global - syahriza, muhammad farid (Maliki Interdisciplinary Journal, 2025)
Strategic management plays a crucial role in determining the direction of an organization amidst the rapid and complex changes in the business environment, especially in the context of globalization marked by technological advances and market liberalization. This article aims to examine the basic concepts, stages, and implementation of strategic management in the global business arena, using a descriptive qualitative approach through a literature review. The results of the study indicate that an effective strategy must be able to integrate global efficiency with local adaptation, supported by an in-depth analysis of the internal and external environment. The company’s ability to balance between standardization and adaptation is the key to successful and sustainable global strategy. The Wheelen & Hunger strategic management model describes a multi-layered process that includes three main stages: the input stage (data collection), the matching stage (strategy formulation using tools such as SWOT and BCG Matrix), and the decision stage (strategic decision making). SWOT analysis, BCG Matrix, and Porter’s Five Forces have proven to be important instruments in identifying opportunities, threats, and the strategic position of the company. Examples of global strategy implementation by multinational companies such as Samsung, Unilever, and Telkom Indonesia demonstrate the importance of technology-based product innovation, market research, and flexibility to achieve sustainable competitive advantage. Therefore, strategic management is not just a long-term plan, but a continuous and adaptive cycle that is essential for maintaining existence and winning global competition.